Painting Lessons On Ceramic Plates For Grade VIII SLB-E Students At The Provincial Level Of North Sumatra - Natalia, Natalia; Mesra, Mesra; Sugito, Sugito; Azis, Adek Cerah Kurnia; Yumielda, Vivi Destri (Institut Seni Indonesia Padang Panjang, 2024)
This research was motivated by class VIII SLB-E students who were less motivated to learn painting because the media used was less varied. Hence, students were less interested in painting. This research aims to assess the painting work of SLB-E students at the North Sumatra Province level based on four aspects: theme, technique, neatness and beauty. The method used is descriptive qualitative research with data collection techniques through demonstrations, practical tests, observation and documentation. The research sample consisted of 18 Deaf Grade VIII students. The target to be achieved in implementing painting learning is to increase motivation, creativity and students' interest in practising. The expected achievements in this research are the ability to express ideas according to the theme, master painting techniques with alternative media such as ceramic plates, and produce neat and beautiful work. The research results showed an average score of 86 (Very Good), with details: theme (82), technique (87), neatness (88), and beauty (85). In conclusion, students can use ceramic plates as media to apply these four aspects in painting.